Neural decoding on imbalanced calcium imaging data with a network of support vector machines. (3rd April 2021) - Lee, Kyunghun; Wu, Xiaomin; Lee, Yaesop; Lin, Da-Ting; Bhattacharyya, Shuvra S.; Chen, Rong
Abstract : We present a novel neural decoding system for calcium imaging data. Miniature calcium imaging is of great utility for examining population neural activity of animals. Our neural decoding system is developed using a carefully designed support vector machine subsystem together with dataflow-based techniques for system design, which capture the high-level structure of the application and enable powerful system-level analysis and optimization. Also, we introduce a framework for handling imbalanced data. This addresses a problem of imbalanced datasets, which arises commonly in neural decoding applications, as well as in a wide variety of other applications in biomedical engineering and advanced robotics. We developed an ensemble learning-based method to tackle this problem. The proposed framework systemically incorporates two heterogeneous model characteristics into a combined model. Through extensive experiments, we evaluate the proposed system using calcium imaging datasets in which neural activities of D1 medium spiny neurons in the dorsal striatum were recorded. The results show that the F 1 score of the proposed system is significantly better than those of previously developed neural decoding systems for calcium imaging. GRAPHICAL ABSTRACT: